Socio-Economic Determinants of the Adoption of Good Cashew Production Practices in Benin - Cossi Léonard Hinnou; Alfred Ayedoun; Sabine Tede; Esdras Abréwa Rêmilokoun Obossou (Journal of Agricultural Extension, 2022)
Although cashew is of strategic socio-economic interest in Benin, yields remain low due to biotic and abiotic constraints. Thus, good cashew production practices have been disseminated to improve productivity. The study analysed the determinants of the adoption of good cashew production practices among 395 cashew farmers. The determinants of the adoption of good practices were assessed through a multivariate probit regression model. Results show that the adoption of thinning, firebreak and pest management practices were positively influenced by cashew tree plantation size, producers' membership in a group and their perception of good practices, income from cashew production, and the number of years of experience in cashew production. Policies and programs to promote cashew nut cultivation must emphasize capacity building for producers, taking into account their access to productive resources.